The Effect of Skill Performance – Like Exercises on the Improvement of Horizontal bar Shtalder and Endo Skill in Artistic Gymnastics for Men - Saeed , Wajdan; Abdulaa, Ahmed; Sakran , Jamal (Journal of Physical Education, 2023)
The research aimed at identifying the effect of special exercises that resemble skill performance on the Shtadler and Endo skills on horizontal bars. The researchers hypothesized that these special exercises that resemble skill performance have significant effect on improving Endo and shtadler skills in men’s horizontal bar. They used the experimental method on (6) Iraqi national league gymnasts aged 9 – 13 years. The researchers concluded that these special exercises that resemble skill performance have significant effect on the development of Endo and shtalder skills in men’s horizontal bar. Finally, they recommended the necessity of using aiding tools and apparatuses to improve Edno and shtalder skill in horizontal bar.